Quality of dispatcher-assisted vs. automated external defibrillator-guided cardiopulmonary resuscitation: a randomised simulation trial. (January 2021) - Ballesteros-Peña, Sendoa; Fernández-Aedo, Irrintzi; Vallejo-De la Hoz, Gorka; Etayo Sancho, Alejandro; Alonso Pinillos, Asier
Abstract : Background: Quality of hands-only cardiopulmonary resuscitation (CPR) is an important determinant of resuscitation outcome for cardiac arrest patients cared for by lay rescuers. We designed a simulation trial to assess and compare the quality of CPR among untrained lay people under two different scenarios: automated external defibrillator (AED)-guided and dispatcher-assisted CPR. Patients and methods: A simulation study was performed involving 42 volunteers selected by non-probabilistic sampling. Participants were randomized into two CPR simulation scenarios with a manikin: (A) AED-guided CPR and (T) dispatcher-assisted CPR. The quality of CPR was evaluated by metric monitoring of the chest compressions and timing of actions. Content analysis of the telephone instructions was performed by two independent researchers using a checklist. Results: CPR was started in 20 of the 21 cases in scenario A and in all cases in scenario T. In total, 12 053 chest compressions were applied, 57.6% corresponding to scenario A. The proportion of compressions that were of an adequate depth was low in both cases, 15.3% in scenario A vs. 31.7% in scenario T ( P < 0.001), while complete chest recoil was allowed in 66 and 72% ( P < 0.001) of compressions, respectively. The AED advised to shock 91 times, and shocks were delivered in all cases. Conclusions: Although guided CPR helps untrained people to initiate resuscitation manoeuvres, the quality of CPR was poor in both groups. Telephone guidance improved the proportion of compressions that achieved adequate chest compression and recoil but did not optimise the compression rate.